Vanadium-based materials as electrode materials in sodium-ion batteries - Hartung, Steffen Uwe (2018)
Sodium-ion batteries have advantages over the wide-spread lithium-ion batteries with regard to cost and kinetics. However, low cycling stability is still a common problem for many electrode materials. Thus, identification of suitable materials and understanding of the respective charge-storage mechanisms are necessary. This work presents investigations on vanadium-based electrode materials in sodium-ion batteries. Reasons for the observed decrease in capacity during cycling are identified and successful strategies to improve cycling stability are presented. This doctoral thesis comprises the scientific publications resulting from my work as a research associate at TUM CREATE. After an introduction to sodium-ion batteries, the main experimental methods employed in this work are described. Subsequently, my four scientific publications, as well as one further publication in which my contribution was crucial, are presented. The thesis is concluded with a discussion of the described results.